Market Transaction Model Design Applicable for Both Plan and Market Environment of China’s Renewable Energy - Li, Gengyin; Li, Guodong; Zhou, Ming (Frontiers in Energy Research, 2022)
China’s electricity market is undergoing a rapid development stage from plan to market and will exist in plan and market models for a long time. Based on the status quo of China’s power plan and market in-depth, this paper has studied and put forward a kind of market transaction mechanism adapted to the plan and market models of China. The mechanism arranges a priority generation plan first to match the priority electricity plan. Especially for renewable energy generation output greater than planned value, it carries out priority arrangement of renewable energy generation to guarantee its reliable consumption. Then medium- and long-term market transactions and incremental spot market transactions are carried out. This paper detailed design operational processes such as priority plan, medium- and long-term, spot (i.e., day-ahead, intraday, and real time), auxiliary services, and balance stages. Finally, based on actual data of the provincial electricity market, the calculation and analysis are carried out to verify that the method proposed in this paper can effectively reduce market imbalance and promote renewable energy consumption, which has a certain practical value for China’s electricity market development.